Administration and Therapeutic Drug Monitoring of β-lactams and Vancomycin in Critical Care Units in Colombia: The ANTIBIOCOL Study - Yuli V. Fuentes; Jhosep Blanco; Diana Marcela Díaz-Quijano; Sharon Lechtig-Wasserman; Hans Liebisch-Rey; Nicolas Díaz-Pinilla; Peter Vergara-Ramirez; Rosa-Helena Bustos (MDPI AG, 2021)
Therapeutic drug monitoring (TDM) and continuous infusion strategies are effective interventions in clinical practice, but these practices are still largely unknown in Colombia, especially in the critical care setting. This study aims to describe the practices involved in the administration and TDM of β-lactams and vancomycin reported by specialists in critical care in Colombia and to explore the factors that are related to the use of extended infusion. An online nationwide survey was applied to 153 specialists, who were selected randomly. A descriptive, bivariate analysis and a logistic regression model were undertaken. In total, 88.9% of the specialists reported TDM availability and 21.57% reported access to results within 6 h. TDM was available mainly for vancomycin. We found that 85.62% of the intensivists had some type of institutional protocol; however, only 39.22% had a complete and socialized protocol. The odds of preferring extended infusions among those who did not have institutional protocols were 80% lower than those with complete protocols, OR 0.2 (95% CI: 0.06−0.61). The most important perceived barriers to performing continuous infusions and TDM were the lack of training and technologies. This pioneering study in Colombia could impact the quality of care and outcomes of critically ill patients in relation to the threat of antimicrobial resistance.